Uma proposta de aplicação de webquests no processo de ensino e aprendizagem de Física - Silva Filho, Edmo Magalhães (2016)
This work aims to analyze the use of technological resources WebQuest in physics classes, in order to verify their behavior as a facilitating tool in the learning process. Given the presence of technological resources, such as computer and Internet in the daily lives of all, it is proposed a teaching method based on this exchange between the classroom of physics and the use of virtual tools. To develop this proposal, a survey was conducted among 131 students of College of the Military Police of Ceará, one of the most prestigious schools in the state public network of Ceará; this research addressed the demand for the inclusion of new technologies in the daily physics classes for high school and primary school. The interviewed students showed interest and excitement in the activities carried out with the WebQuest methodology, because until then, these resources were not used in physics classes. The proposed solution led to the use of dynamic and interactive technology tools in class.